The Boundaries of the Force Majeure Defense in Civil Disputes: A Study of Decision Number 162/PDT/2021/PT DPS - Mutiara, I Made Cinta; Akbar, Ferdi Raditya; Aini, Hanifah Qurrotu; Andriyanto, Fransisca Dealova; Gladys, Juniartha; Azhar, Muhamad Davindra; Alfarel, Muhammad Arkan; Azmina, Fayza; Rizkianti, Wardani (Rechtsvinding, 2025)
A contract forms the legal relationship between parties that creates binding rights and obligations as regulated in Article 1338 of the Indonesian Civil Code (KUHPer). However, the performance of a contract may be hindered by events beyond human can control, known as force majeure. Under Articles 1244 and 1245 of the Civil Code, a party who fails to fulfill its obligations due to force majeure may be released from liability for damages. This study aims to analyze the limits of force majeure as a legal defense in civil disputes through a case study of Decision Number 162/PDT/2021/PT DPS between PT Royal Pacific Nusantara and PT Lorenz Marble. The research employs a normative legal method with statutory, case, and conceptual approaches, using primary legal materials such as the Civil Code and court decisions, as well as secondary materials including legal books and scholarly journals related to force majeure. The results indicate that the court recognized the Covid-19 pandemic as a relative force majeure, which temporarily hinders the performance of contractual obligations but does not permanently extinguish them. The judges found that the defendant was not negligent, as they demonstrated good faith and efforts to fulfill obligations despite global disruptions. Thus, the boundaries of force majeure as a defense are determined by the causal relationship between extraordinary events and the inability to perform, along with the good faith of the party invoking the defense.